2000
DOI: 10.1046/j.1432-1033.2000.01326.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic conformation of lipid A is responsible for agonistic and antagonistic activity

Abstract: Lipopolysaccharides (LPS, endotoxin) represent a major virulence factor of Gram-negative bacteria, which can cause septic shock in mammals, including man. The lipid anchor of LPS to the bacterial outer membrane, lipid A, exhibits a peculiar chemical structure, harbours the`endotoxic principle' of LPS and is also responsible for the expression of pathophysiological effects. Chemically modified lipid A can be endotoxically inactive, but may express strong antagonistic activity against endotoxically active LPS. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
89
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(100 citation statements)
references
References 32 publications
(49 reference statements)
8
89
0
Order By: Relevance
“…Lipid A, which anchors the LPS to the outer membrane of bacteria, is the endotoxic part of LPS. The most endotoxic form of lipid A consists of a hexa-acylated glucosamine disaccharide phosphorylated at the 1 and 4′ position with acyl chains from 12 to 14 carbons in length and an asymmetric (4/2) distribution (14, 16, 17). This structure is common to Escherichia coli and Shigella (18, 19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid A, which anchors the LPS to the outer membrane of bacteria, is the endotoxic part of LPS. The most endotoxic form of lipid A consists of a hexa-acylated glucosamine disaccharide phosphorylated at the 1 and 4′ position with acyl chains from 12 to 14 carbons in length and an asymmetric (4/2) distribution (14, 16, 17). This structure is common to Escherichia coli and Shigella (18, 19).…”
Section: Introductionmentioning
confidence: 99%
“…The total number and the length of acyl chains plus the presence of the two phosphates in positions 1 and 4′ are critical factors for full lipid A activation of human TLR4/MD-2 (14, 16, 17, 19). Changes to the structure of the lipid A, either by removal of critical components or by replacement of one of the acyl chains by a different acyl residue, affects the binding and recognition by TLR4 and results in a lower endotoxicity in vitro (14, 16).…”
Section: Introductionmentioning
confidence: 99%
“…The role of acyl chains and head groups on the inflammatory response initiated by lipid A has been elucidated by Seydel and coworkers, who have determined its conformation and supramolecular structure (23)(24)(25)(26). Using biophysical approaches, Seydel and his group have written extensively about the relationship between the conformation of lipid A and its ability to act as an agonist and antagonist (23).…”
mentioning
confidence: 99%
“…Using biophysical approaches, Seydel and his group have written extensively about the relationship between the conformation of lipid A and its ability to act as an agonist and antagonist (23). They have shown that lipid A modifications in the acyl chain number, distribution of the chains (symmetrical or asymmetrical), and head group substitution were accompanied by a change in the tilt angle of the backbone with respect to the acyl chains, which impact the conformation of the lipid A structure and, potentially, the ability to engage Toll-like receptor 4 (TRL4).…”
mentioning
confidence: 99%
See 1 more Smart Citation